2009
DOI: 10.4055/cios.2009.1.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Vesicocutaneous Fistula Presenting Groin Abscess and Chronic Osteomyelitis in Pubic Bone

Abstract: The authors report a case of bladder fistula associated with a medial thigh cutaneous fistula and chronic osteomyelitis of the pubic bone 11 years after surgery for a pelvic bone fracture and bladder rupture. In the presenting case, despite the clinical suspicion, none of the diagnostic tools demonstrated the bladder fistula preoperatively. This case suggests that bladder repair should be prepared, even if the bladder fistula cannot be confirmed by imaging studies because the amount of urine leakage can be min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Prostatectomy-related vesico-cutaneous fistula negatively affects the patient's quality of life and increases the health care costs as much as BPH. In the literature, case reports on vesico-cutaneous fistula demonstrate an association with vulvar cancer (Lau and Cheng, 1998), groin surgery (Kishore et al, 2005), gigantic urinary bladder stones (Kobori et al, 2007), pelvic fracture (Kim et al, 2009), total hip prosthesis (Gallmetzer et al, 1999), cesarian section (Toufique and Merani, 2011), trauma (Priyadarshi et al, 2013) and adjuvant radiotherapy of prostate cancer (Hennessey et al, 2013). We found no report on open prostatectomy-related vesico-cutaneous fistula within the literature.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Prostatectomy-related vesico-cutaneous fistula negatively affects the patient's quality of life and increases the health care costs as much as BPH. In the literature, case reports on vesico-cutaneous fistula demonstrate an association with vulvar cancer (Lau and Cheng, 1998), groin surgery (Kishore et al, 2005), gigantic urinary bladder stones (Kobori et al, 2007), pelvic fracture (Kim et al, 2009), total hip prosthesis (Gallmetzer et al, 1999), cesarian section (Toufique and Merani, 2011), trauma (Priyadarshi et al, 2013) and adjuvant radiotherapy of prostate cancer (Hennessey et al, 2013). We found no report on open prostatectomy-related vesico-cutaneous fistula within the literature.…”
Section: Introductionmentioning
confidence: 76%
“…In the literature, case reports on vesico-cutaneous fistula demonstrate an association with vulvar cancer (Lau and Cheng, 1998), groin surgery (Kishore et al, 2005), gigantic urinary bladder stones (Kobori et al, 2007), pelvic fracture (Kim et al, 2009), total hip prosthesis (Gallmetzer et al, 1999), cesarian section (Toufique and Merani, 2011), trauma (Priyadarshi et al, 2013) and adjuvant radiotherapy of prostate cancer (Hennessey et al, 2013). In the literature, case reports on vesico-cutaneous fistula demonstrate an association with vulvar cancer (Lau and Cheng, 1998), groin surgery (Kishore et al, 2005), gigantic urinary bladder stones (Kobori et al, 2007), pelvic fracture (Kim et al, 2009), total hip prosthesis (Gallmetzer et al, 1999), cesarian section (Toufique and Merani, 2011), trauma (Priyadarshi et al, 2013) and adjuvant radiotherapy of prostate cancer (Hennessey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vesicocutaneos fistula following road traffic accident/pelvic trauma is uncommon, but this has been previously documented [6] [7]. We hereby report a case of vesicocutaneous fistula following road traffic accident/pelvic trauma and share our experience in the management of this case.…”
Section: Introductionmentioning
confidence: 84%
“…Imaging modalities such as intravenous urography, computerized tomography scan and magnetic resonance imaging may be useful in management of patients with vesicocutaneous fistula [1] [2] [5]. Failure to demonstrate vesicocutaneous fistula using imaging studies does not confirm its absence [6]. This is of particular importance in a low resource setting as this case can be effectively managed without sophisticated investigation modalities following a clinical diagnosis of this disease.…”
Section: Case Presentationmentioning
confidence: 99%
“…VCF of thigh after trauma was first reported by Kosaka et al which presented 7 years after pelvic injury and there are still very few such reported cases in literature. 8 10 11 These fistulas usually develop at a variable time duration after trauma and are usually preceded with thigh swelling or abscess formation followed by spontaneous rupture. To the best of our knowledge, VCFs of bilateral thighs have never been reported.…”
Section: Discussionmentioning
confidence: 99%